Identifikasi dan Perbandingan Komposisi Kepadatan Mesodebris pada Pantai Wisata - Fadhila Nurhayati; Irwan Ramadhan Ritonga; Ristiana Eryati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aimed to determine the type, composition and density of mesodebris based on seasonal differences (periods I and II). Sampling was conducted using the purposive sampling method. There were 5 lanes of transects randomised to determine the sub-transect box. Mesodebris samples were taken by excavating surface sediments (Â± 3 cm) and filtered with 0.5 cm x 0.5 cm size at Lamaru beach, Balikpapan City. All samples were collected, grouped and counted to determine the type, number, weight and density of mesodebris. The analysis results showed that 6 types of mesodebris were found in the study site such as plastic, plastic foam, glass, cloth, wood and rubber. The highest mesodebris composition for the number category was plastic (80%) in period II, while the highest weight composition was found in period I at 51%. The density of mesodebris with the most number category was found in period II (1.64 amount/m2). From the results of the study it can be concluded that there was no significant difference in the mesodebris density between periods I and II at Lamaru Tourism Beach, Balikpapan City. The main sources of mesodebris in the study area come from tourist activities, local residents' activities on land, and water runoff from the Manggar River. Keywords: Balikpapan, Density, Mesodebris, Season